D e c e n t r a l i z at i o n P o l i c i e s i n A s i a n D e v e l o p m e n t - Shinichi Ichimura, Roy Bahl (World Scientific Publishing, 2009)
This volume deals with the important subject of Political and Fiscal Decentralization, which is now under discussion and reform by governments in many Asian countries including Japan, India, Indonesia, and China. The progress with fiscal decentralization in Asia has attracted much attention from policy makers and scholars around the world as they consider their own reform programs. In the early stage of economic development and nation-building, the concentration of power and resources was undoubtedly a necessity to politically unite the nation and to make the economic takeoff possible. As a result, the political system of a new nation-state was usually organized under an authoritarian central government. With economic development, however, civil society and the business sector demanded that the government offer better public services and utilities as well as better opportunities for employment and business development. Particularly as the regional disparities in living conditions kept widening, the people and businesses in outer regions desired governments to be closer and more responsive to them and demanded decentralization of political and fiscal administration. Recognizing this, bureaucrats and politicians began to seriously search for the ways and means of political and fiscal decentralization. For instance, in Indonesia even in the 1970s and the 80s, to talk about the possibility of federal system was a taboo for the newly borne nation. Now, as one article in this book shows, Indonesia has adopted a decentralized political and fiscal system.